Preparation method of anode foil of aluminum electrolytic capacitor
By adding a water-soluble pore-forming agent to the aluminum paste of the anode foil of the aluminum electrolytic capacitor, forming a porous structure, and then applying a protective film layer on the surface to perform oblique rolling treatment, the problems of poor bending performance and surface defects of the anode foil are solved, and higher mechanical properties and production quality are achieved.
Patent Information
- Application Number
- CN202510196033.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The bending resistance of existing aluminum electrolytic capacitor anode foil is poor and cannot meet the needs of mechanical processing. At the same time, the surface is prone to scratching and powder loss, which affects flatness and integrity.
By adding a water-soluble pore-forming agent to the aluminum slurry, a porous aluminum foil body is formed, and a protective film layer is coated on the surface, and the rolling process is performed by oblique rolling, and finally a sintered foil with irregular multi-directional cracks are formed by sintering.
It improves the bending resistance of the anode foil, reduces surface defects, ensures the integrity and smoothness of the surface, solves the adhesion problem, and improves production quality.
Smart Images

Figure CN119673673A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of capacitors, and in particular to a method for preparing an anode foil of an aluminum electrolytic capacitor. Background Art
[0002] Aluminum electrolytic capacitors have the advantages of small size, low cost, and large capacity, and are widely used in the electronics industry. With the development of technology, higher requirements are placed on the overall performance and size of devices used in automotive electronics, household appliances, and industrial control. The performance and quality of aluminum electrolytic capacitors also need to match the overall performance of the devices, prompting aluminum electrolytic capacitors to further develop in the direction of high capacity, miniaturization, and greening. The requirements for the bending resistance of the anode foil of aluminum electrolytic capacitors are also getting higher and higher.
[0003] At present, the anode foil of aluminum electrolytic capacitors can be prepared by sintering a porous aluminum powder layer on the surface of the aluminum foil substrate, but the anode foil formed has poor bending resistance and cannot meet the requirements of mechanical processing. In order to improve the bending resistance of the anode foil, cracks can be processed on the surface of the foil by an inclined roller (diameter 6mm~20mm), and the foil passes around the conveying roller and the roller. The conveying roller is used to transmit the foil forward. The foil passes around the roller at an angle. Since the bending contact surface is at an angle with the width direction of the foil, corresponding cracks are generated when it passes through the roller bending. Multiple groups of rollers can be set to process multiple cracks at the same time; a number of balls (diameter 2mm~4mm) that can rotate around their own spheres can also be provided on the circumferential surface of the roller (diameter 8mm~12mm), and the balls are in contact with the electrode foil. The foil surface of the electrode foil and the balls that can rotate in multiple directions around their own spheres are relatively rolled and subjected to the interaction of the rolling tension, thereby forming multi-directional cracks on the foil surface of the electrode foil. However, the surface of the anode foil prepared by the above two methods is prone to scratches and powder loss, and the flatness and integrity of the anode foil surface cannot be guaranteed, which leads to easy adhesion of the foil when the aluminum foil is rolled and sintered; in addition, the existing technology uses small-diameter rollers (20 mm and below), which have poor rigidity and are easy to bend during continuous foil processing, which easily leads to foil wrinkles, making it impossible to produce anode foil with a smooth surface and good anti-bending performance.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In view of this, a method for preparing an anode foil of an aluminum electrolytic capacitor is provided, which can improve the bending resistance of the anode foil, reduce defects on the surface of the anode foil, and ensure the integrity and flatness of the surface of the anode foil.
[0006] Other features and advantages of the present disclosure will become apparent from the following detailed description, or may be learned in part by the practice of the present disclosure.
[0007] According to one aspect of the present disclosure, a method for preparing an anode foil of an aluminum electrolytic capacitor is provided, the method comprising: Step S1: preparing aluminum paste, wherein the aluminum paste comprises a mixed solution and solid aluminum-containing powder, wherein the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder comprises aluminum powder and a water-soluble pore-forming agent; Step S2: providing an aluminum foil substrate, coating the aluminum paste on the surface of the aluminum foil substrate, and performing a drying process to form an aluminum foil blank; Step S3: washing the dried aluminum foil blank with water, and drying it to obtain a porous aluminum foil blank; Step S4: heat treating the porous aluminum foil blank; Step S5: coating a thin film solution on the surface of the porous aluminum foil blank after the heat treatment, and performing a drying treatment to form a protective film layer on the surface of the porous aluminum foil blank; Step S6: using a rolling mill to perform a rolling process on the porous aluminum foil blank having the protective film layer in a skew rolling manner to obtain an initial anode foil; Step S7: sintering the initial anode foil to remove the protective film layer to form a sintered foil.
[0008] In an exemplary embodiment of the present disclosure, the rolling mill is one of a two-roll rolling mill, a three-roll rolling mill or a four-roll rolling mill, the rolling mill has a rolling roller pressure of 5 μm to 15 μm, and a roller diameter of 65 mm to 600 mm. In step S6, the porous aluminum foil blank having the protective film layer is rolled by the rolling mill in a skew rolling manner to obtain an initial anode foil. The method includes: The porous aluminum foil blank having the protective film layer is subjected to a first rolling treatment, wherein the first rolling treatment is to repeatedly roll the porous aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 20° to 70° with the length direction of the porous aluminum foil blank; The porous aluminum foil blank with the protective film layer is then subjected to a second rolling treatment, wherein the second rolling treatment is to repeatedly roll the porous aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 110° to 160° with the length direction of the porous aluminum foil blank.
[0009] In an exemplary embodiment of the present disclosure, the film solution is an aqueous solution prepared by one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; in step S5, the film solution is coated on the surface of the porous aluminum foil blank after heat treatment, and the method includes: The porous aluminum foil blank is coated with the thin film solution on both sides by using a blade coating or screen printing method; the thickness of the protective film layer on each side of the porous aluminum foil blank is the same, and the thickness of the protective film layer on each side of the porous aluminum foil blank is 5μm~30μm.
[0010] In an exemplary embodiment of the present disclosure, the mass fraction of the water-soluble pore-forming agent to the solid aluminum-containing powder is 0.5% to 4%; the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80 to 250); The water-soluble pore-forming agent is one or more of a water-soluble neutral salt, a water-soluble starch, and a water-soluble resin; The water-soluble neutral salt is one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate; The water-soluble starch is one or more of modified corn starch, modified potato starch, modified sweet potato starch, modified cassava starch, modified wheat starch, and modified mung bean starch; The water-soluble resin is one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxyethyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose.
[0011] In an exemplary embodiment of the present disclosure, in step S3, the dried aluminum foil blank is washed with water and dried to obtain a porous aluminum foil blank, comprising: The aluminum foil blank is cleaned with deionized water at 10° C. to 80° C. by immersion or ultrasonic cleaning. The cleaned aluminum foil blank is dried at a drying temperature of 40° C. to 120° C.
[0012] In an exemplary embodiment of the present disclosure, in step S4, the porous aluminum foil blank is subjected to heat treatment, comprising: In an air atmosphere, heating the porous aluminum foil blank from room temperature to 300° C. to 500° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 1 h to 8 h; In a nitrogen, argon or vacuum atmosphere, the porous aluminum foil blank is continuously heated to 570° C. to 600° C. at a heating rate of 0.1° C. / min to 20° C. / min, and kept at this temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
[0013] In an exemplary embodiment of the present disclosure, the mass ratio of the solvent, the binder, and the additive in the mixed solution is 100:(3-10):(0.5-10); The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or both of terpineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol; The binder is one or two of ethyl cellulose and polyvinyl butyral; The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent.
[0014] In an exemplary embodiment of the present disclosure, the thickness of the aluminum foil substrate is 20 μm to 60 μm, and the aluminum foil substrate has an upper surface and a lower surface arranged opposite to each other. In step S2, the aluminum foil blank is formed, and the method includes: The aluminum foil substrate is double-sided coated with the aluminum paste to form aluminum paste film layers with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; The aluminum foil substrate with the aluminum paste film layer is dried at a drying temperature of 90° C. to 200° C., and the thickness of the aluminum paste film layer after drying is 50 μm to 60 μm.
[0015] In an exemplary embodiment of the present disclosure, in step S7, the sintering process includes: In a nitrogen, argon or vacuum atmosphere, heating the initial anode foil from room temperature to 610° C. to 650° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
[0016] In an exemplary embodiment of the present disclosure, after step S7, the method further includes: The sintered foil is subjected to a water boiling treatment to form an intermediate anode foil, wherein the water boiling treatment comprises boiling the sintered foil in deionized water at 100° C. for 5 to 15 minutes; Performing a chemical formation treatment on the intermediate anode foil to form an oxide layer on the intermediate anode foil to obtain a target anode foil, wherein the chemical formation treatment has a chemical formation voltage of 200V to 700V; The target anode foil is cleaned and dried.
[0017] The present invention provides a method for preparing an anode foil of an aluminum electrolytic capacitor. The method comprises the following steps: adding a water-soluble pore-forming agent to an aluminum paste, coating the aluminum paste on the surface of an aluminum foil substrate, and drying the aluminum foil blank. The porous aluminum foil blank is then washed and dried to obtain a porous aluminum foil blank. The porous aluminum foil blank is then heat treated and coated with a protective film layer. The porous aluminum foil blank is then rolled and sintered to obtain a sintered foil having irregular multi-directional cracks on the surface and inside. The preparation method adds a water-soluble pore-forming agent to the aluminum paste, which can increase the porosity of the aluminum foil blank, facilitate the subsequent rolling treatment to form internal stress in the aluminum foil blank, so as to form cracks during the sintering process; in addition, the surface and interior of the sintered foil obtained by this method have irregular multi-directional cracks, which can improve the subsequent anti-bending performance of the anode foil; in addition, the preparation method first coats the surface of the porous aluminum foil blank with a protective film layer, and then performs oblique rolling through a rolling mill, which can solve the problem of surface scratching and powdering of the anode foil. The protective film layer can form a gap between adjacent porous aluminum foil blanks, and in the subsequent sintering process, the adhesion between the porous aluminum foil blanks is avoided; in addition, the rolling roller used in the preparation method is a large-diameter roller (diameter of 65mm-300mm), the roller has better rigidity, can effectively improve the foil wrinkle problem caused by roller bending, and improve the production quality of the anode foil. The preparation method can produce an anode foil with a smooth surface and good anti-bending performance.
[0018] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0020] Figure 1 The present invention is a flowchart of a method for preparing an anode foil for an aluminum electrolytic capacitor in an exemplary embodiment of the present invention.
[0021] Figure 2 This is an optical microscope image of the anode foil prepared in Comparative Example 1.
[0022] Figure 3 This is an optical microscope image of the anode foil prepared in Comparative Example 2.
[0023] Figure 4 This is an optical microscope image of the anode foil prepared in Example 1 of the present disclosure. DETAILED DESCRIPTION
[0024] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.
[0025] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.
[0026] Based on this, the present disclosure provides a method for preparing an anode foil of an aluminum electrolytic capacitor, such as Figure 1 As shown, the preparation method includes: step S1 to step S7.
[0027] Wherein, step S1: preparing aluminum paste, the aluminum paste includes a mixed solution and solid aluminum-containing powder, the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder includes aluminum powder and a water-soluble pore-forming agent; Step S2: providing an aluminum foil substrate, coating the aluminum paste on the surface of the aluminum foil substrate to form an aluminum foil blank, and drying the aluminum foil blank; Step S3: washing the dried aluminum foil blank with water, and drying it to obtain a porous aluminum foil blank; Step S4: heat treating the porous aluminum foil blank; Step S5: coating the thin film solution on the surface of the porous aluminum foil blank after the heat treatment, and performing a drying treatment to form a protective film layer on the surface of the porous aluminum foil blank; Step S6: using a rolling mill to perform a rolling process on the porous aluminum foil blank having the protective film layer by means of oblique rolling to obtain an initial anode foil; Step S7: Sintering the initial anode foil to remove the protective film layer to form a sintered foil.
[0028] The present invention provides a method for preparing an anode foil of an aluminum electrolytic capacitor. The method comprises the following steps: adding a water-soluble pore-forming agent to an aluminum paste, coating the aluminum paste on the surface of an aluminum foil substrate, and drying the aluminum foil blank. The porous aluminum foil blank is then washed and dried to obtain a porous aluminum foil blank. The porous aluminum foil blank is then heat treated and coated with a protective film layer. The porous aluminum foil blank is then rolled and sintered to obtain a sintered foil having irregular multi-directional cracks on the surface and inside. The preparation method adds a water-soluble pore-forming agent to the aluminum paste, which can increase the porosity of the aluminum foil blank, facilitate the subsequent rolling treatment to form internal stress in the aluminum foil blank, so as to form cracks during the sintering process; in addition, the surface and interior of the sintered foil obtained by this method have irregular multi-directional cracks, which can improve the subsequent anti-bending performance of the anode foil; in addition, the preparation method first coats the surface of the porous aluminum foil blank with a protective film layer, and then performs oblique rolling through a rolling mill, which can solve the problems of surface scratches, powder loss and wrinkles of the anode foil, and the protective film layer can form a gap between adjacent porous aluminum foil blanks, and in the subsequent sintering process, the adhesion between the porous aluminum foil blanks is avoided; in addition, the rolling roller used in the preparation method is a large-diameter roller (diameter of 65mm-300mm), the roller has better rigidity, can effectively improve the foil wrinkle problem caused by roller bending, and improve the production quality of the anode foil. The preparation method can produce an anode foil with a smooth surface and good anti-bending performance.
[0029] The following will describe in detail the steps of the method for preparing the anode foil of an aluminum electrolytic capacitor provided by the embodiment of the present disclosure in conjunction with the accompanying drawings: In the embodiment provided in the present disclosure, in step S1, aluminum paste is prepared, and the aluminum paste includes a mixed solution and solid aluminum-containing powder, the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder includes aluminum powder and a water-soluble pore-forming agent.
[0030] Among them, the aluminum-containing slurry includes a mixed solution prepared by mixing a solvent, a binder and an additive. The mass ratio of the solvent, the binder and the additive in the mixed solution is 100:(3~10):(0.5~10). For example, the mass ratio of the three can be 100:3:0.5, 100:3:10, 100:10:0.5 or 100:10:10, etc. The mass ratio between the components in the mixed solution can be selected or adaptively adjusted according to the specific type and function of the component.
[0031] The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or two of pineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol. The binder is one or two of ethyl cellulose and polyvinyl butyral. The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent. By controlling the type and mass ratio of each component in the aluminum-containing slurry, the aluminum-containing slurry can have the characteristics of low evaporation rate at room temperature, easy storage, and moderate viscosity. The solvent is easy to volatilize during the drying process, the aluminum-containing slurry has good leveling properties, and there is no or little residue of the binder and additives during the heat treatment process.
[0032] Among them, the aluminum-containing slurry includes solid aluminum-containing powder, and the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80~250). For example, the mass ratio between the two can be 100:80, 100:100, 100:120, 100:140, 100:160, 100:180, 100:200, 100:220, 100:240 or 100:250, etc. The mass ratio between the mixed solution and the solid aluminum-containing powder is within the above range, which can improve the subsequent formation quality of the aluminum foil blank.
[0033] The solid aluminum-containing powder includes aluminum powder, the aluminum particles in the aluminum powder may be spherical or ellipsoidal, and the particle size of the aluminum powder is 0.5 μm (micrometer) to 5 μm, for example, the particle size of the aluminum powder may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc. In the process of preparing the aluminum powder, there may be a variety of aluminum powders of different particle sizes in the solid aluminum-containing powder, and in some exemplary embodiments, the particle sizes of the aluminum powders in the solid aluminum-containing powder may be the same or substantially the same. The mass purity of the aluminum powder is not less than 99.95%, for example, the mass purity of the aluminum powder may be 99.95%, 99.96%, 99.97%, 99.98% or 99.99%, etc.
[0034] The solid aluminum-containing powder includes a water-soluble pore-forming agent, and the mass fraction of the water-soluble pore-forming agent in the solid aluminum-containing powder is 0.5% to 4%. For example, the mass fraction of the water-soluble pore-forming agent in the solid aluminum-containing powder can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%. The water-soluble pore-forming agent can be one or more of a water-soluble neutral salt, a water-soluble starch, and a water-soluble resin.
[0035] Among them, when the water-soluble pore-forming agent is a neutral salt soluble in water, the water-soluble pore-forming agent can be one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate; when the water-soluble pore-forming agent is a water-soluble starch, the water-soluble pore-forming agent can be one or more of modified corn starch, modified potato starch, modified sweet potato starch, modified cassava starch, modified wheat starch, and modified mung bean starch; when the water-soluble pore-forming agent is a water-soluble resin, the water-soluble pore-forming agent can be one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, and hydroxypropyl methyl cellulose.
[0036] By controlling the type and addition amount of each component in the aluminum paste, the aluminum paste has the characteristics of low volatility, easy preservation, and moderate viscosity at room temperature. The solvent is easy to evaporate during the drying process, and the slurry has good leveling properties. The water-soluble pore-forming agent is easy to remove during the water washing process. The anode foil formed subsequently has a higher specific capacity. There is no or little residue of binders and additives in the subsequent heat treatment process.
[0037] In the embodiment provided in the present disclosure, in step S2, an aluminum foil substrate is provided, the aluminum paste is coated on the surface of the aluminum foil substrate to form an aluminum foil blank, and the aluminum foil blank is dried.
[0038] The thickness of the aluminum foil substrate is 20 μm to 60 μm, for example, the thickness of the aluminum foil substrate may be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm, etc. The aluminum foil substrate has an upper surface and a lower surface that are relatively arranged. Since there may be subsequent differences between the parts of the aluminum foil substrate, the thickness of the aluminum foil substrate may refer to one of the maximum distance, the minimum distance or the average distance between the upper surface and the lower surface. In the present disclosure, the thickness of the aluminum foil substrate is taken as the average distance between the upper surface and the lower surface for explanation.
[0039] In some embodiments, in step S2, an aluminum foil blank is formed, including: using an aluminum-containing slurry to double-side coat an aluminum foil substrate to form an aluminum slurry film layer with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; drying the aluminum foil substrate with the aluminum slurry film layer at a drying temperature of 90°C to 200°C.
[0040] Among them, the double-sided coating of the aluminum foil substrate can be carried out by a coating method such as doctor blade coating and screen printing, and an aluminum paste film layer of the same thickness is formed on the upper surface and the lower surface of the aluminum foil substrate. The thickness of the aluminum paste film layer after drying is 50μm~60μm, for example, it can be 50μm, 52μm, 54μm, 56μm, 58μm or 60μm, etc. By controlling the thickness of the aluminum foil substrate and the aluminum paste film layer, a porous layer of appropriate thickness is formed on both sides of the aluminum foil blank, thereby improving the ductility of the aluminum foil blank in the subsequent rolling process.
[0041] It should be noted that the same thickness of the aluminum paste film layer formed on the upper surface and the lower surface of the aluminum foil substrate means that the thickness of the two is exactly the same or approximately the same. Due to process errors, the difference in thickness between the two is within 1 μm, and the thickness of the two can be considered to be the same.
[0042] After the aluminum film layer is formed on the surface of the aluminum foil substrate, the aluminum foil substrate is dried, wherein the drying temperature can be 90°C to 200°C, for example, the drying temperature can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc. The specific drying temperature can be adaptively adjusted according to the thickness of the aluminum film layer. For example, when the thickness of the aluminum film layer is thick, the drying temperature can be appropriately increased to shorten the drying time and improve the efficiency. The preparation method can control the drying temperature so that the slurry has good leveling during the drying process and the solvent evaporates more thoroughly.
[0043] In the embodiment provided in the present disclosure, in step S3, the dried aluminum foil blank is washed with water and dried to obtain a porous aluminum foil blank.
[0044] In some embodiments, step S3 includes: cleaning the aluminum foil blank with deionized water at 10°C to 80°C, using a cleaning method of immersion or ultrasonic cleaning; and drying the cleaned aluminum foil blank at a drying temperature of 40°C to 120°C.
[0045] The cleaning temperature is 10°C to 80°C, for example, 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, etc. By controlling the temperature of the deionized water, the water-soluble pore-forming agent is removed and the formed aluminum foil body is not easy to fall off. The drying temperature is 40°C to 120°C, for example, 40°C, 60°C, 80°C, 100°C or 120°C, etc. By controlling the drying temperature, the aluminum foil body is easy to dry.
[0046] In the embodiment provided in the present disclosure, in step S4, the porous aluminum foil blank is heat treated.
[0047] In some embodiments, the heat treatment in step S4 includes: in an air atmosphere, heating the porous aluminum foil blank from room temperature to 300°C~500°C at a heating rate of 0.1°C / min~20°C / min, and keeping it warm for 1h~8h; in a nitrogen, argon or vacuum atmosphere, continuing to heat the porous aluminum foil blank to 570°C~600°C at a heating rate of 0.1°C / min~20°C / min, and keeping it warm for 4h~12h; cooling with the furnace after the insulation is completed. Among them, the room temperature can be 20~25°C. By controlling the heating rate, insulation temperature and insulation time during the heat treatment process, the residual amount of binder and additive in the aluminum foil blank is reduced, or the binder and additive in the aluminum foil blank are free of residue after heat treatment.
[0048] In the embodiment provided in the present disclosure, in step S5, a thin film solution is coated on the surface of the porous aluminum foil blank after heat treatment, and a drying treatment is performed to form a protective film layer on the surface of the porous aluminum foil blank.
[0049] The film solution is an aqueous solution prepared from one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol and polyvinyl pyrrolidone.
[0050] A thin film solution is coated on the surface of a porous aluminum foil blank. The method includes: using a form of doctor blade coating or screen printing to coat the porous aluminum foil blank with a thin film solution on both sides; the thickness of the protective film layer on each side of the porous aluminum foil blank is the same. The thickness of the protective film layer on each side of the porous aluminum foil blank is 5μm~30μm, for example, the thickness of the protective film layer can be 5μm, 10μm, 15μm, 20μm, 25μm or 30μm. The same thickness of the protective film layer on each side of the porous aluminum foil blank means that the thickness of the two protective film layers is exactly the same or approximately the same. Due to process errors, the difference in thickness of the two protective film layers is within the range of 1μm, and the thickness of the two can be considered to be the same. The method controls the composition of the thin film solution and the thickness of the protective film layer, and the protective film layer is not easy to fall off during the subsequent rolling process to protect the aluminum slurry film layer from being scratched or powdered, and the protective film layer is easier to remove during the subsequent sintering process, and will not have an adverse effect on the overall structure of the anode foil.
[0051] In the embodiment provided in the present disclosure, in step S6, the porous aluminum foil blank with the protective film layer is rolled by a rolling mill in a skew rolling manner to obtain an initial anode foil.
[0052] The rolling mill can be one of a two-roll rolling mill, a three-roll rolling mill or a four-roll rolling mill. In order to improve the rolling quality of the rolling mill on the porous aluminum foil blank, the rolling mill roll pressure can be 5μm~15μm, for example, the rolling mill roll pressure can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm, etc. In order to avoid the porous aluminum foil blank from powdering or scratching during the rolling process, the rolling mill roll diameter can be 65mm~600mm, for example, the rolling mill roll diameter can be 65mm, 100mm, 150mm, 200mm, 250mm, 300mm, 350mm, 400mm, 450mm, 500mm, 550mm or 600mm, etc.
[0053] In some embodiments, a porous aluminum foil blank having a protective film layer is rolled by a rolling mill in a skew rolling manner to obtain an initial anode foil, the method comprising: The porous aluminum foil blank with a protective film layer is subjected to a first rolling treatment, in which the first rolling treatment is repeated 2 to 20 times when the axial direction of the roller and the length direction of the aluminum foil blank are 20° to 70°; the porous aluminum foil blank with a protective film layer is subjected to a second rolling treatment, in which the second rolling treatment is repeated 2 to 20 times when the axial direction of the roller and the length direction of the aluminum foil blank are 110° to 160°.
[0054] Among them, in the first rolling process, the axis direction of the roller and the length direction of the porous aluminum foil blank can be 20°~70°, for example, it can be 20°, 30°, 40°, 50°, 60° or 70°, and the number of rolling times can be 2 to 20 times; in the second rolling process, the axis direction of the roller and the length direction of the porous aluminum foil blank are 110°~160°, for example, it can be 110°, 120°, 130°, 140°, 150° or 160°, and the number of rolling times can be 2 to 20 times. In some exemplary embodiments, there is a correlation between the rolling angle of the rolling mill, the roller pressure, the roller diameter and the number of rolling times. When the roller diameter is large, one or more of the pressure, the rolling angle or the number of rolling times can be increased to improve the rolling efficiency and the rolling quality.
[0055] The method controls the rolling angle of the rolling mill, the downward pressure of the rolling mill rolls and the diameter of the rolling mill rolls, so that the protective film layer on the surface of the porous aluminum foil blank is not easy to fall off during the rolling process, the aluminum slurry film layer is not easy to be scratched and does not lose powder, and suitable internal stress can be generated inside the aluminum slurry film layer, so that the aluminum slurry film layer produces irregular multi-directional cracks in the subsequent sintering process, thereby improving the bending resistance of the anode foil.
[0056] In the embodiment provided by the present disclosure, in step S7, the initial anode foil is sintered to remove the protective film layer to form a sintered foil.
[0057] The initial anode foil is sintered, including: heating the initial anode foil from room temperature to 610°C~650°C at a heating rate of 0.1°C / min~20°C / min in a nitrogen, argon or vacuum atmosphere, and keeping the temperature for 4h~12h; cooling with the furnace after the insulation is completed.
[0058] The parameters of the sintering treatment are as follows: in nitrogen, argon or vacuum atmosphere, the heating rate is 0.1°C / min~20°C / min, for example, the heating rate can be 0.1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min, etc.; the initial anode foil is heated from room temperature to a holding temperature, the holding temperature is 610°C~650°C, for example, the holding temperature can be 610°C, 620°C, 630°C, 640°C or 650°C, etc.; the holding time is 4h~12h, for example, the holding time can be 4h, 6h, 8h, 10h or 12h, etc. In the embodiment provided by the present disclosure, the room temperature can be 20°C~25°C.
[0059] By adjusting and controlling the parameters of the sintering treatment, such as the heating rate, sintering atmosphere, holding temperature and holding time, the protective film layer on the surface of the sintered foil can be removed cleanly, and at the same time, the surface of the sintered foil can be made flat and non-sticky, thereby ensuring the flatness and integrity of the surface of the sintered foil. Irregular multi-directional cracks can be generated on the surface and inside of the sintered foil to improve the bending resistance of the subsequently formed anode foil.
[0060] In the embodiment provided in the present disclosure, after step S7, the method further includes: boiling the sintered foil to form an intermediate anode foil; performing a chemical treatment on the intermediate anode foil to form an oxide layer on the intermediate anode foil to obtain a target anode foil; and cleaning and drying the target anode foil.
[0061] The boiling treatment includes boiling the sintered foil in deionized water at 100°C for 5 to 15 minutes. The temperature of the deionized water may be 100°C in a strict sense, but due to temperature error, the temperature of the deionized water may also be within the range of 100°C±1°C, which may be considered as the temperature of the deionized water required during the boiling treatment. The boiling treatment time is 5 to 15 minutes, for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes.
[0062] By adjusting and controlling the time and temperature of the water boiling treatment, a hydrated aluminum oxide layer of suitable thickness can be formed on the surface of the aluminum powder particles in the sintered foil, which is beneficial to the formation of an oxide layer in the subsequent chemical treatment.
[0063] The formation treatment includes performing a formation treatment on the intermediate anode foil under the condition that the formation voltage is 200V to 700V. The formation voltage is 200V to 700V, for example, the formation voltage can be 200V, 300V, 400V, 500V, 600V or 700V, etc. The hydrated aluminum oxide layer can be converted into an oxide layer through the formation treatment, wherein the oxide layer is an aluminum oxide film layer.
[0064] By adjusting and controlling the formation voltage, anode foils with various rated withstand voltage requirements can be produced.
[0065] The target anode foil is cleaned and dried to obtain a target anode foil with better cleanliness.
[0066] The disclosed embodiment also provides an aluminum electrolytic capacitor, which includes an anode foil prepared by the above method. The capacitor has good mechanical properties and good overall device performance.
[0067] The following is a further description of the method for preparing the anode foil provided by the present disclosure through specific examples: Comparative Example 1 Step 1: Mix and stir the solvent (butyl acetate and propylene glycol), binder (polyvinyl butyral), and additives (polyether defoamer and acrylate leveling agent) in a mass ratio of 80:20:5:0.5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0068] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0069] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0070] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 8 hours, and cool with the furnace after the insulation is completed.
[0071] Step 5: Process the heat-treated aluminum foil obtained in step 4 through a roller with a diameter of 12 mm to produce cracks on the foil surface. The process is as follows: first, the aluminum foil is passed through the roller at an angle of 20° between the length direction of the aluminum foil and the axis direction of the roller, and this is repeated 20 times; then, the aluminum foil is passed through the roller at an angle of 140° between the length direction of the aluminum foil and the axis direction of the roller, and this is repeated 20 times.
[0072] Step 6: Sinter the aluminum foil obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 630° C. at a heating rate of 10° C. / min in argon gas, keeping the temperature for 8 hours, and cooling with the furnace after the end of the temperature keeping.
[0073] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0074] Comparative Example 2 Step 1: Mix and stir the solvent (butyl acetate and propylene glycol), binder (polyvinyl butyral), and additives (polyether defoamer and acrylate leveling agent) in a mass ratio of 80:20:5:0.5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0075] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0076] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0077] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 8 hours, and cool with the furnace after the insulation is completed.
[0078] Step 5: The heat-treated aluminum foil obtained in step 4 is passed through a roller (12 mm in diameter) with a ball (2 mm in diameter) on the circumferential surface that can rotate around its own ball center to process cracks on the foil surface. The process is: first, the aluminum foil is passed through the roller at an angle of 20° between the length direction and the axis direction of the roller, and this is repeated 20 times; then, the aluminum foil is passed through the roller at an angle of 140° between the length direction and the axis direction of the roller, and this is repeated 20 times.
[0079] Step 6: Sinter the aluminum foil obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 630° C. at a heating rate of 10° C. / min in argon gas, keeping the temperature for 8 hours, and cooling with the furnace after the end of the temperature keeping.
[0080] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0081] Comparative Example 3 Step 1: Mix and stir the solvent (butyl acetate and propylene glycol), binder (polyvinyl butyral), and additives (polyether defoamer and acrylate leveling agent) in a mass ratio of 80:20:5:0.5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain aluminum paste (also referred to as paste in the following embodiments); wherein the aluminum powder has a particle size of 0.5 μm to 5 μm, a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0082] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0083] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0084] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 8 hours, and cool with the furnace after the insulation is completed.
[0085] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the film thickness is 15 μm.
[0086] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 630°C at a heating rate of 10°C / min in argon gas, keeping the temperature for 8 hours, and cooling with the furnace after the end of the heat preservation.
[0087] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0088] Example 1 Step 1: Mix and stir the solvent (butyl acetate and propylene glycol), binder (polyvinyl butyral), and additives (polyether defoamer and acrylate leveling agent) in a mass ratio of 80:20:5:0.5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0089] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0090] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0091] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 8 hours, and cool with the furnace after the insulation is completed.
[0092] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the film thickness is 15 μm.
[0093] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 20 times at an angle of 20° between the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 20 times at an angle of 140° between the length direction and the roller axis direction; the roller pressure during the rolling process (also referred to as the pressure in the following embodiments) is 5 μm; the roller diameter is 300 mm; and the rolling mill is a two-roll rolling mill.
[0094] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 630° C. at a heating rate of 10° C. / min in argon gas, keeping the temperature for 8 hours, and cooling with the furnace after the end of the temperature keeping.
[0095] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0096] When the bending strength test was carried out using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Control Example 1 had 118 longitudinal bending times, 66 transverse bending times, and a static specific capacity of 0.926 μF / cm2; the anode foil obtained in Control Example 2 had 124 longitudinal bending times, 58 transverse bending times, and a static specific capacity of 0.934 μF / cm2; the anode foil obtained in Control Example 3 had 5 longitudinal bending times, 9 transverse bending times, and a static specific capacity of 0.956 μF / cm2; the anode foil obtained in Example 1 had 136 longitudinal bending times, 72 transverse bending times, and a static specific capacity of 0.951 μF / cm2; under the condition of the same number of treatments, the performance (static specific capacity and number of bending times) of the anode foil prepared in Example 1 was higher than that of the anode foil prepared in Control Example 1 and Control Example 2.
[0097] also, Figure 2, Figure 3 and Figure 4 The optical microscope images of the anode foils obtained by the preparation methods provided in Comparative Example 1, Comparative Example 2 and Example 1 are shown respectively. Figure 2 and Figure 3 It can be seen that the anode foils obtained in Comparative Example 1 and Comparative Example 2 both have irregular multi-directional cracks, and the surfaces of the anode foils both have scratches, powder loss and other defects. Figure 4 It can be seen that the anode foil obtained in Example 1 has irregular multi-directional cracks, and the surface quality of the anode foil is good, without defects such as scratches and powder loss. The preparation method of Example 1 can obtain an anode foil with good anti-bending performance.
[0098] Comparative Example 4 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 0.5%.
[0099] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0100] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 10°C; the washing method is soaking; and the drying temperature is 120°C.
[0101] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 20°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 20°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0102] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is screen printing; and the film thickness is 5 μm.
[0103] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650°C at a heating rate of 0.1°C / min in vacuum, keeping the temperature for 2 hours, and cooling with the furnace after the end of the heat preservation.
[0104] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0105] Example 2 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:10:10:10:5:5:1:1:5:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 0.5%.
[0106] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0107] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 10°C; the washing method is soaking; and the drying temperature is 120°C.
[0108] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 20°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 20°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0109] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is screen printing; and the film thickness is 5 μm.
[0110] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled twice at 70° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled twice at 110° in the length direction and the roller axis direction; the downward pressure in the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roll rolling mill.
[0111] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650° C. at a heating rate of 0.1° C. / min in a vacuum, keeping the temperature for 2 hours, and cooling with the furnace after the end of the heat preservation.
[0112] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0113] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Example 4 was bent once in the longitudinal direction and three times in the transverse direction, and the static specific capacity was 1.002 μF / cm 2 The anode foil obtained in Example 2 was bent 179 times in the longitudinal direction and 69 times in the transverse direction, and the static specific capacity was 0.998 μF / cm 2 .
[0114] Comparative Example 5 Step 1: Mix and stir the solvent (pinene alcohol and ethylene glycol), binder ethyl cellulose, and additive silicone defoamer at a mass ratio of 50:50:3:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch, and polyethylene glycol) at a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch, and polyethylene glycol in the solid aluminum-containing powder are 2.5%, 1%, and 0.5%, respectively.
[0115] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0116] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is ultrasonic cleaning; and the drying temperature is 40°C.
[0117] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keep warm for 1 hour; then heat to 600°C in nitrogen at a heating rate of 0.1°C / min, and keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0118] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is a polyethylene glycol solution; the coating method is blade coating; and the film thickness is 30 μm.
[0119] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 610°C at a heating rate of 20°C / min in nitrogen, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0120] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0121] Example 3 Step 1: Mix and stir the solvent (pinene alcohol and ethylene glycol), binder ethyl cellulose, and additive silicone defoamer at a mass ratio of 50:50:3:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch, and polyethylene glycol) at a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch, and polyethylene glycol in the solid aluminum-containing powder are 2.5%, 1%, and 0.5%, respectively.
[0122] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0123] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is ultrasonic cleaning; and the drying temperature is 40°C.
[0124] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keep warm for 1 hour; then heat to 600°C in nitrogen at a heating rate of 0.1°C / min, and keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0125] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is a polyethylene glycol solution; the coating method is blade coating; and the film thickness is 30 μm.
[0126] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at 40° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at 160° in the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a four-roll mill.
[0127] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 610° C. at a heating rate of 20° C. / min in nitrogen, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0128] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0129] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 5 was 14 times, the number of transverse bending times was 15 times, and the static specific capacity was 0.922 μF / cm 2 The anode foil obtained in Example 3 was bent 169 times in the longitudinal direction and 98 times in the transverse direction, and the static specific capacity was 0.919 μF / cm 2 .
[0130] Comparative Example 6 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and ethylene glycol), binder polyvinyl butyral, and additives (organic silicone defoamer and triethanolamine dispersant) in a mass ratio of 40:20:40:3:0.5:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium chloride) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.99%, and a mass fraction of potassium chloride in the solid aluminum-containing powder of 4%.
[0131] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0132] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is soaking; and the drying temperature is 50°C.
[0133] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 1°C / min, and keep warm for 1 hour; then heat to 600°C in vacuum at a heating rate of 1°C / min, keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0134] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose; the coating method is screen printing; and the film thickness is 20 μm.
[0135] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650°C at a heating rate of 1°C / min in vacuum, keeping the temperature for 4 hours, and cooling with the furnace after the end of the heat preservation.
[0136] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0137] Example 4 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and ethylene glycol), binder polyvinyl butyral, and additives (organic silicone defoamer and triethanolamine dispersant) in a mass ratio of 40:20:40:3:0.5:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium chloride) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.99%, and a mass fraction of potassium chloride in the solid aluminum-containing powder of 4%.
[0138] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0139] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is soaking; and the drying temperature is 50°C.
[0140] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 1°C / min, and keep warm for 1 hour; then heat to 600°C in vacuum at a heating rate of 1°C / min, keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0141] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose; the coating method is screen printing; and the film thickness is 20 μm.
[0142] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at 40° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at 140° in the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a three-roll mill.
[0143] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650° C. at a heating rate of 1° C. / min in vacuum, keeping the temperature for 4 hours, and cooling with the furnace after the end of the heat preservation.
[0144] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0145] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 6 was 12 times, the number of transverse bending times was 16 times, and the static specific capacity was 2.914 μF / cm 2 The anode foil obtained in Example 4 was bent 141 times in the longitudinal direction and 91 times in the transverse direction, and the static specific capacity was 2.892 μF / cm 2 .
[0146] Comparative Example 7 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, propylene glycol), binder ethyl cellulose, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 50:30:20:5:0.5:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0147] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0148] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 60°C; the washing method is ultrasonic cleaning; and the drying temperature is 70°C.
[0149] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 350°C in air at a heating rate of 5°C / min, and keep warm for 6 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0150] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is polyvinyl butyral and polyvinyl pyrrolidone; the coating method is blade coating; the film thickness is 15 μm.
[0151] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 630°C at a heating rate of 5°C / min in argon gas, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0152] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0153] Example 5 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, propylene glycol), binder ethyl cellulose, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 50:30:20:5:0.5:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 1%.
[0154] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0155] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 60°C; the washing method is ultrasonic cleaning; and the drying temperature is 70°C.
[0156] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 350°C in air at a heating rate of 5°C / min, and keep warm for 6 hours; then heat to 580°C in vacuum at a heating rate of 10°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0157] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is polyvinyl butyral and polyvinyl pyrrolidone; the coating method is blade coating; the film thickness is 15 μm.
[0158] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 20 times at 30° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 20 times at 150° in the length direction and the roller axis direction; the pressing amount during the rolling process is 15 μm; the roller diameter is 300 mm; the rolling mill is a two-roll rolling mill.
[0159] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 630° C. at a heating rate of 5° C. / min in argon gas, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0160] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0161] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 7 was 7 times, the number of transverse bending times was 8 times, and the static specific capacity was 2.941 μF / cm 2 The anode foil obtained in Example 5 was bent 175 times in the longitudinal direction and 75 times in the transverse direction, and the static specific capacity was 2.939 μF / cm 2 .
[0162] Comparative Example 8 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:25:5:3:5:1:1:4 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 0.2%, 0.2% and 0.1%, respectively.
[0163] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60μm.
[0164] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 30°C; the washing method is ultrasonic cleaning; and the drying temperature is 110°C.
[0165] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 10°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 5°C / min, keep warm for 6 hours, and cool with the furnace after the insulation is completed.
[0166] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl methylcellulose and hydroxypropyl methylcellulose; the coating method is screen printing; and the film thickness is 10 μm.
[0167] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 610°C at a heating rate of 20°C / min in argon gas, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0168] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100° C. to obtain an anode foil. The water boiling treatment uses 100° C. deionized water for 5 minutes; the chemical forming treatment uses 100 g / L boric acid solution at a forming voltage of 200 V.
[0169] Example 6 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, triethanolamine dispersant and silane coupling agent) in a mass ratio of 40:30:25:5:3:5:1:1:4 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 0.2%, 0.2% and 0.1%, respectively.
[0170] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60μm.
[0171] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 30°C; the washing method is ultrasonic cleaning; and the drying temperature is 110°C.
[0172] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 10°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 5°C / min, keep warm for 6 hours, and cool with the furnace after the insulation is completed.
[0173] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl methylcellulose and hydroxypropyl methylcellulose; the coating method is screen printing; and the film thickness is 10 μm.
[0174] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled twice at 60° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled twice at 120° in the length direction and the roller axis direction; the pressing amount during the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roll rolling mill.
[0175] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 610° C. at a heating rate of 20° C. / min in argon gas, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0176] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0177] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Example 8 was bent four times in the longitudinal direction and three times in the transverse direction, and the static specific capacity was 3.054 μF / cm 2The anode foil obtained in Example 6 was bent 185 times in the longitudinal direction and 92 times in the transverse direction, and the static specific capacity was 3.051 μF / cm 2 .
[0178] Comparative Example 9 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol, propylene glycol and glycerol), binder ethyl cellulose and additives (silicone defoamer and silane coupling agent) in a mass ratio of 30:30:30:10:8:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 2%.
[0179] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0180] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is soaking; and the drying temperature is 60°C.
[0181] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 15°C / min, and keep warm for 4 hours; then heat to 600°C in nitrogen at a heating rate of 3°C / min, and keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0182] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is polyvinyl butyral; the coating method is blade coating; and the film thickness is 30 μm.
[0183] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 610°C at a heating rate of 5°C / min in vacuum, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0184] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0185] Example 7 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol, propylene glycol and glycerol), binder ethyl cellulose and additives (silicone defoamer and silane coupling agent) in a mass ratio of 30:30:30:10:8:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 2%.
[0186] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0187] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 80°C; the washing method is soaking; and the drying temperature is 60°C.
[0188] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 15°C / min, and keep warm for 4 hours; then heat to 600°C in nitrogen at a heating rate of 3°C / min, and keep warm for 4 hours, and cool with the furnace after the insulation is completed.
[0189] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is polyvinyl butyral; the coating method is blade coating; and the film thickness is 30 μm.
[0190] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at 45° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at 135° in the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 65 mm; the rolling mill is a three-roll mill.
[0191] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 610° C. at a heating rate of 5° C. / min in a vacuum, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0192] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0193] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 9 was 17 times, the number of transverse bending times was 14 times, and the static specific capacity was 0.776 μF / cm 2 The anode foil obtained in Example 7 was bent 149 times in the longitudinal direction and 109 times in the transverse direction, and the static specific capacity was 0.771 μF / cm 2 .
[0194] Comparative Example 10 Step 1: Mix and stir the solvent (butyl acetate, propylene glycol and glycerol), binder polyvinyl butyral, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 90:5:5:5:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are 1.5% and 0.5%, respectively.
[0195] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0196] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0197] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 3°C / min, and keep warm for 6 hours; then heat to 580°C in vacuum at a heating rate of 15°C / min, keep warm for 10 hours, and cool with the furnace after the insulation is completed.
[0198] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol and hydroxypropyl methylcellulose; the coating method is screen printing; and the film thickness is 20 μm.
[0199] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 640°C at a heating rate of 10°C / min in argon gas, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0200] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100° C. to obtain an anode foil. The water boiling treatment uses 100° C. deionized water for 5 minutes; the chemical forming treatment uses 100 g / L boric acid solution at a forming voltage of 700 V.
[0201] Example 8 Step 1: Mix and stir the solvent (butyl acetate, propylene glycol and glycerol), binder polyvinyl butyral, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 90:5:5:5:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are 1.5% and 0.5%, respectively.
[0202] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0203] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 50°C; the washing method is soaking; and the drying temperature is 80°C.
[0204] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 3°C / min, and keep warm for 6 hours; then heat to 580°C in vacuum at a heating rate of 15°C / min, keep warm for 10 hours, and cool with the furnace after the insulation is completed.
[0205] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol and hydroxypropyl methylcellulose; the coating method is screen printing; and the film thickness is 20 μm.
[0206] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 20 times at an angle of 20° between the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 20 times at an angle of 110° between the length direction and the roller axis direction; the pressing amount during the rolling process is 5 μm; the roller diameter is 300 mm; and the rolling mill is a two-roll rolling mill.
[0207] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 640° C. at a heating rate of 10° C. / min in argon gas, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0208] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0209] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 10 was 8 times, the number of transverse bending times was 12 times, and the static specific capacity was 0.788 μF / cm 2 The anode foil obtained in Example 8 was bent 143 times in the longitudinal direction and 55 times in the transverse direction, and the static specific capacity was 0.781 μF / cm 2 .
[0210] Comparative Example 11 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, dispersant triethanolamine and silane coupling agent) in a mass ratio of 50:40:10:3:7:1:1:2:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch, polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 0.2%, 0.1% and 0.2%, respectively.
[0211] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0212] Step 3: Wash the aluminum foil blank obtained in step 2 with water and dry it. The washing process is to wash the aluminum foil blank with deionized water at 10°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0213] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 20°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 20°C / min, and keep warm for 6 hours, and cool with the furnace after the insulation is completed.
[0214] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is blade coating; the film thickness is 25 μm.
[0215] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650°C at a heating rate of 0.1°C / min in nitrogen, keeping the temperature for 4 hours, and cooling with the furnace after the end of the heat preservation.
[0216] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0217] Example 9 Step 1: Mix and stir the solvent (butyl acetate, ethylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, acrylate leveling agent, dispersant triethanolamine and silane coupling agent) in a mass ratio of 50:40:10:3:7:1:1:2:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch, polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 0.2%, 0.1% and 0.2%, respectively.
[0218] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0219] Step 3: Wash the aluminum foil blank obtained in step 2 with water and dry it. The washing process is to wash the aluminum foil blank with deionized water at 10°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0220] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 20°C / min, and keep warm for 8 hours; then heat to 570°C in argon at a heating rate of 20°C / min, and keep warm for 6 hours, and cool with the furnace after the insulation is completed.
[0221] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is blade coating; the film thickness is 25 μm.
[0222] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled twice at 70° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled twice at 160° in the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 600 mm; the rolling mill is a two-roller rolling mill.
[0223] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 650° C. at a heating rate of 0.1° C. / min in nitrogen, keeping the temperature for 4 hours, and cooling with the furnace after the end of the heat preservation.
[0224] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0225] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Example 11 was bent three times in the longitudinal direction and twice in the transverse direction, and the static specific capacity was 0.803 μF / cm 2 The anode foil obtained in Example 9 was bent 136 times in the longitudinal direction and 72 times in the transverse direction, and the static specific capacity was 0.795 μF / cm 2 .
[0226] Comparative Example 12 Step 1: Mix and stir the solvent (pinene alcohol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, dispersant triethanolamine and silane coupling agent) in a mass ratio of 95:5:8:2:2:2:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 2%.
[0227] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0228] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 70°C; the washing method is soaking; and the drying temperature is 80°C.
[0229] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 590°C in vacuum at a heating rate of 0.1°C / min, and keep warm for 4 hours, and then cool with the furnace after the insulation is completed.
[0230] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is polyvinyl alcohol; the coating method is screen printing; and the film thickness is 15 μm.
[0231] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 630°C at a heating rate of 20°C / min in argon gas, keeping the temperature for 10 hours, and cooling with the furnace after the end of the heat preservation.
[0232] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0233] Example 10 Step 1: Mix and stir the solvent (pinene alcohol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additives (polyether defoamer, dispersant triethanolamine and silane coupling agent) in a mass ratio of 95:5:8:2:2:2:2 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 2%.
[0234] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 90°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0235] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 70°C; the washing method is soaking; and the drying temperature is 80°C.
[0236] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 400°C in air at a heating rate of 10°C / min, and keep warm for 4 hours; then heat to 590°C in vacuum at a heating rate of 0.1°C / min, and keep warm for 4 hours, and then cool with the furnace after the insulation is completed.
[0237] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is polyvinyl alcohol; the coating method is screen printing; and the film thickness is 15 μm.
[0238] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 20 times at 60° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 20 times at 160° in the length direction and the roller axis direction; the pressing amount during the rolling process is 5 μm; the roller diameter is 200 mm; the rolling mill is a two-roll rolling mill.
[0239] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 630° C. at a heating rate of 20° C. / min in argon gas, keeping the temperature for 10 hours, and cooling with the furnace after the end of the heat preservation.
[0240] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0241] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 12 was 10 times, the number of transverse bending times was 11 times, and the static specific capacity was 0.961 μF / cm 2 The anode foil obtained in Example 10 was bent 152 times in the longitudinal direction and 84 times in the transverse direction, and the static specific capacity was 0.953 μF / cm 2 .
[0242] Comparative Example 13 Step 1: Mix and stir the solvent (butyl acetate and ethylene glycol), binder (ethyl cellulose and polyvinyl butyral), and additive (organic silicone defoamer and silane coupling agent) in a mass ratio of 50:50:6:2:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:200 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are 0.3% and 0.2%, respectively.
[0243] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0244] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 60°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0245] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 350°C in air at a heating rate of 20°C / min, and keep warm for 4 hours; then heat to 600°C in argon at a heating rate of 3°C / min, and keep warm for 4 hours, and then cool with the furnace after the insulation is completed.
[0246] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the film thickness is 15 μm.
[0247] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650°C at a heating rate of 10°C / min in vacuum, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0248] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0249] Embodiment 11 Step 1: Mix and stir the solvent (butyl acetate and ethylene glycol), binder (ethyl cellulose and polyvinyl butyral), and additive (organic silicone defoamer and silane coupling agent) in a mass ratio of 50:50:6:2:0.5:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent sodium chloride and modified corn starch) in a mass ratio of 100:200 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are 0.3% and 0.2%, respectively.
[0250] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 20μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0251] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 60°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0252] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 350°C in air at a heating rate of 20°C / min, and keep warm for 4 hours; then heat to 600°C in argon at a heating rate of 3°C / min, and keep warm for 4 hours, and then cool with the furnace after the insulation is completed.
[0253] Step 5: Coat the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and dry it. The thin film solution is ethyl cellulose and polyvinyl pyrrolidone; the coating method is screen printing; and the film thickness is 15 μm.
[0254] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at an angle of 20° between the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at an angle of 160° between the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 65 mm; and the rolling mill is a three-roll mill.
[0255] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 650° C. at a heating rate of 10° C. / min in a vacuum, keeping the temperature for 6 hours, and cooling with the furnace after the end of the heat preservation.
[0256] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 15 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0257] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Example 13 was bent twice in the longitudinal direction and four times in the transverse direction, and the static specific capacity was 0.799 μF / cm 2 The anode foil obtained in Example 11 was bent 155 times in the longitudinal direction and 72 times in the transverse direction, and the static specific capacity was 0.798 μF / cm 2 .
[0258] Comparative Example 14 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicon defoamer and triethanolamine dispersant) in a mass ratio of 20:40:36:2:2:9:1:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 1%, 0.5% and 0.5%, respectively.
[0259] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60μm.
[0260] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 20°C; the washing method is ultrasonic cleaning; and the drying temperature is 120°C.
[0261] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 2°C / min, and keep warm for 2 hours; then heat to 600°C in vacuum at a heating rate of 5°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0262] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is screen printing; and the film thickness is 25 μm.
[0263] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 620°C at a heating rate of 1°C / min in vacuum, keeping the temperature for 10 hours, and cooling with the furnace after the end of the heat preservation.
[0264] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0265] Example 12 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol and glycerol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicon defoamer and triethanolamine dispersant) in a mass ratio of 20:40:36:2:2:9:1:1:3 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:150 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 1%, 0.5% and 0.5%, respectively.
[0266] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60μm.
[0267] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 20°C; the washing method is ultrasonic cleaning; and the drying temperature is 120°C.
[0268] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 2°C / min, and keep warm for 2 hours; then heat to 600°C in vacuum at a heating rate of 5°C / min, keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0269] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is screen printing; and the film thickness is 25 μm.
[0270] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at 40° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at 110° in the length direction and the roller axis direction; the pressing amount during the rolling process is 15 μm; the roller diameter is 100 mm; the rolling mill is a two-roll rolling mill.
[0271] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 620° C. at a heating rate of 1° C. / min in a vacuum, keeping the temperature for 10 hours, and cooling with the furnace after the end of the heat preservation.
[0272] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0273] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 14 was 8 times, the number of transverse bending times was 11 times, and the static specific capacity was 2.969 μF / cm 2 The anode foil obtained in Example 12 was bent 136 times in the longitudinal direction and 72 times in the transverse direction, and the static specific capacity was 2.967 μF / cm 2 .
[0274] Comparative Example 15 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), binder polyvinyl butyral, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 4%.
[0275] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0276] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 30°C; the washing method is soaking; and the drying temperature is 60°C.
[0277] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 5°C / min, and keep warm for 4 hours; then heat to 590°C in nitrogen at a heating rate of 0.1°C / min, and keep warm for 12 hours, and then cool with the furnace after the insulation is completed.
[0278] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is hydroxyethyl methylcellulose; the coating method is screen printing; and the film thickness is 30 μm.
[0279] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 610°C at a heating rate of 0.1°C / min in argon gas, keeping the temperature for 2 hours, and cooling with the furnace after the end of the heat preservation.
[0280] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0281] Example 13 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate and glycerol), binder polyvinyl butyral, and additives (silicone defoamer and acrylate leveling agent) in a mass ratio of 20:75:5:4:1:5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent potassium sulfate) in a mass ratio of 100:250 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm, a mass purity of 99.95%, and a mass fraction of potassium sulfate in the solid aluminum-containing powder of 4%.
[0282] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 30μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 55μm.
[0283] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 30°C; the washing method is soaking; and the drying temperature is 60°C.
[0284] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 450°C in air at a heating rate of 5°C / min, and keep warm for 4 hours; then heat to 590°C in nitrogen at a heating rate of 0.1°C / min, and keep warm for 12 hours, and then cool with the furnace after the insulation is completed.
[0285] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is hydroxyethyl methylcellulose; the coating method is screen printing; and the film thickness is 30 μm.
[0286] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled twice at 60° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled twice at 110° in the length direction and the roller axis direction; the pressing amount during the rolling process is 15 μm; the roller diameter is 600 mm; the rolling mill is a two-roll rolling mill.
[0287] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 610° C. at a heating rate of 0.1° C. / min in argon gas, keeping the temperature for 2 hours, and cooling with the furnace after the end of the heat preservation.
[0288] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 700V.
[0289] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 15 was 18 times, the number of transverse bending times was 15 times, and the static specific capacity was 0.747 μF / cm 2The anode foil obtained in Example 13 has a longitudinal bending frequency of 157 times, a transverse bending frequency of 97 times, and a static specific capacity of 0.750 μF / cm 2 .
[0290] Comparative Example 16 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol), binder ethyl cellulose, and additive silicone defoamer at a mass ratio of 50:10:40:6:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent sodium chloride, modified corn starch) at a mass ratio of 100:200 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 0.25%.
[0291] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0292] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 70°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0293] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keep warm for 2 hours; then heat to 580°C in argon at a heating rate of 5°C / min, and keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0294] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is hydroxyethyl cellulose and hydroxyethyl methyl cellulose; the coating method is screen printing; and the film thickness is 15 μm.
[0295] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 650°C at a heating rate of 15°C / min in nitrogen, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0296] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0297] Embodiment 14 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol), binder ethyl cellulose, and additive silicone defoamer at a mass ratio of 50:10:40:6:0.5 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder and water-soluble pore-forming agent sodium chloride, modified corn starch) at a mass ratio of 100:200 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.95%, and the mass fractions of sodium chloride and modified corn starch in the solid aluminum-containing powder are both 0.25%.
[0298] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 150°C, the thickness of the aluminum foil substrate is 60 μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 60 μm.
[0299] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 70°C; the washing method is ultrasonic cleaning; and the drying temperature is 100°C.
[0300] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 500°C in air at a heating rate of 0.1°C / min, and keep warm for 2 hours; then heat to 580°C in argon at a heating rate of 5°C / min, and keep warm for 12 hours, and cool with the furnace after the insulation is completed.
[0301] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a thin film solution and drying. The thin film solution is hydroxyethyl cellulose and hydroxyethyl methyl cellulose; the coating method is screen printing; and the film thickness is 15 μm.
[0302] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 15 times at an angle of 20° between the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 15 times at an angle of 135° between the length direction and the roller axis direction; the pressing amount during the rolling process is 5 μm; the roller diameter is 500 mm; and the rolling mill is a two-roll rolling mill.
[0303] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 650° C. at a heating rate of 15° C. / min in nitrogen, keeping the temperature for 12 hours, and cooling with the furnace after the end of the keeping temperature.
[0304] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 10 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 520V.
[0305] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the anode foil obtained in Example 16 was bent once in the longitudinal direction and once in the transverse direction, and the static specific capacity was 1.189 μF / cm 2 The anode foil obtained in Example 14 was bent 157 times in the longitudinal direction and 92 times in the transverse direction, and the static specific capacity was 1.188 μF / cm 2 .
[0306] Comparative Example 17 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicone defoamer and acrylic leveling agent) in a mass ratio of 20:30:45:5:5:5:1:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 1%, 0.5% and 0.5%, respectively.
[0307] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0308] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 40°C; the washing method is soaking; and the drying temperature is 80°C.
[0309] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 1°C / min, and keep warm for 1 hour; then heat to 570°C in nitrogen at a heating rate of 10°C / min, keep warm for 10 hours, and cool with the furnace after the insulation is completed.
[0310] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is blade coating; the film thickness is 10 μm.
[0311] Step 6: Sinter the aluminum foil with the protective film layer on the surface obtained in step 5. The sintering is carried out in a bell-type furnace, and the sintering process is: heating to 610°C at a heating rate of 20°C / min in argon gas, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0312] Step 7: The sintered foil obtained in step 6 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100° C. to obtain an anode foil. The water boiling treatment uses 100° C. deionized water for 5 minutes; the chemical forming treatment uses 100 g / L boric acid solution at a forming voltage of 200 V.
[0313] Embodiment 15 Step 1: Mix and stir the solvent (pinene alcohol, diethylene glycol butyl ether acetate, ethylene glycol, propylene glycol), binder (ethyl cellulose and polyvinyl butyral), additive (organic silicone defoamer and acrylic leveling agent) in a mass ratio of 20:30:45:5:5:5:1:6 to obtain a mixed solution. Mix and stir the mixed solution with solid aluminum-containing powder (aluminum powder, water-soluble pore-forming agent sodium sulfate, modified potato starch and polyethylene glycol) in a mass ratio of 100:80 to obtain a slurry; wherein the aluminum powder has a particle size of 0.5μm~5μm and a mass purity of 99.99%, and the mass fractions of sodium sulfate, modified potato starch and polyethylene glycol in the solid aluminum-containing powder are 1%, 0.5% and 0.5%, respectively.
[0314] Step 2: Apply the slurry obtained in step 1 on the upper surface of the aluminum foil substrate with a scraper and dry it; after turning it 180°, apply the slurry on the current upper surface of the aluminum foil substrate with a scraper and dry it to obtain an aluminum foil blank. The drying temperature is 200°C, the thickness of the aluminum foil substrate is 60μm, and the thickness of the aluminum paste coated on the upper and lower surfaces after drying is 50μm.
[0315] Step 3: Wash and dry the aluminum foil blank obtained in step 2. The washing process is to wash the aluminum foil blank with deionized water at 40°C; the washing method is soaking; and the drying temperature is 80°C.
[0316] Step 4: heat-treat the porous aluminum foil blank obtained in step 3. The heat treatment is carried out in a bell-type furnace, and the heat treatment process is: first, heat from room temperature to 300°C in air at a heating rate of 1°C / min, and keep warm for 1 hour; then heat to 570°C in nitrogen at a heating rate of 10°C / min, keep warm for 10 hours, and cool with the furnace after the insulation is completed.
[0317] Step 5: coating the upper and lower surfaces of the heat-treated aluminum foil obtained in step 4 with a film solution and drying. The film solution is polyvinyl alcohol, hydroxyethyl cellulose and hydroxypropyl methyl cellulose; the coating method is blade coating; the film thickness is 10 μm.
[0318] Step 6, rolling the aluminum foil with the protective film layer on the surface obtained in step 5. The rolling is oblique rolling, and the rolling process is: first, the aluminum foil with the protective film layer on the surface is rolled 10 times at 45° in the length direction and the roller axis direction, and then the aluminum foil with the protective film layer on the surface is rolled 10 times at 160° in the length direction and the roller axis direction; the pressing amount during the rolling process is 10 μm; the roller diameter is 400 mm; the rolling mill is a two-roller rolling mill.
[0319] Step 7: Sinter the rolled aluminum foil obtained in step 6. The sintering is carried out in a bell-type furnace, and the sintering process is as follows: heating to 610° C. at a heating rate of 20° C. / min in argon gas, keeping the temperature for 12 hours, and cooling with the furnace after the end of the heat preservation.
[0320] Step 8: The sintered foil obtained in step 7 is subjected to water boiling treatment and chemical forming treatment, washed with deionized water, and dried at 100°C to obtain an anode foil. The water boiling treatment uses 100°C deionized water for 5 minutes; the chemical forming treatment uses 100g / L boric acid solution at a forming voltage of 200V.
[0321] When the bending strength test was performed using a chuck with a curvature radius of 3.5 mm, the number of longitudinal bending times of the anode foil obtained in Example 17 was 12 times, the number of transverse bending times was 8 times, and the static specific capacity was 2.442 μF / cm 2 The anode foil obtained in Example 15 was bent 171 times in the longitudinal direction and 94 times in the transverse direction, and the static specific capacity was 2.434 μF / cm 2 .
[0322] Table 1 shows the performance test results of the anode foils prepared in Comparative Example 1 to Comparative Example 17 and Example 1 to Example 15.
[0323] Table 1
[0324] It can be seen from Table 1 that the static specific capacity of the anode foil prepared in Example 1 by using the inclined roller treatment is 0.926 μF / cm 2 , the number of longitudinal bending times is 118 times, and the number of transverse bending times is 66 times; the static specific capacity of the anode foil prepared in Example 2, which is treated by a roller having a ball that can rotate around its own ball center and is arranged on the circumferential surface of the inclined setting, is 0.934μF / cm 2 The number of longitudinal bending is 124 times, and the number of transverse bending is 58 times; the anode foil prepared in Example 1 by oblique rolling by a rolling mill has a static specific capacity of 0.951 μF / cm 2 The number of longitudinal bending times is 136 times, and the number of transverse bending times is 72 times; under the same number of treatments, the performance (static specific capacity and number of bending times) of the anode foil prepared in Example 1 is higher than that of the anode foil prepared in Control Example 1 and Control Example 2.
[0325] In addition, the anode foils without rolling treatment prepared in Control Example 3-Control Example 17 have poor transverse and longitudinal bending resistance, and the number of bending times is less than 20 times; the anode foils prepared in Example 1-Example 15 using a rolling mill for oblique rolling have a transverse bending number of more than 50 times and a longitudinal bending number of more than 100 times. By comparing Control Example 3-Control Example 17 with Example 1-Example 15, it can be seen that under the same test conditions, the bending times of the anode foil in the example are increased by more than 300% compared with the anode foil in the control example, which greatly improves the transverse and longitudinal bending resistance of the anode foil and meets the requirements of mechanical processing. In addition, the anode foils in Example 1-Example 15 also have a large static specific capacity, which meets the requirements of subsequent capacitor performance improvement. Therefore, the preparation method of the anode foil provided in the present disclosure can improve the bending resistance of the anode foil, thereby improving the overall performance of the device.
[0326] It should be noted that, although the steps of the method for preparing the anode foil of an aluminum electrolytic capacitor in the present disclosure are described in a specific order in the accompanying drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0327] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
Claims
1. A method for preparing an anode foil for an aluminum electrolytic capacitor, characterized in that: include: Step S1: preparing aluminum paste, wherein the aluminum paste comprises a mixed solution and solid aluminum-containing powder, wherein the mixed solution is prepared by mixing a solvent, a binder and an additive, and the solid aluminum-containing powder comprises aluminum powder and a water-soluble pore-forming agent; Step S2: providing an aluminum foil substrate, coating the aluminum paste on the surface of the aluminum foil substrate, and performing a drying process to form an aluminum foil blank; Step S3: washing the dried aluminum foil blank with water, and drying it to obtain a porous aluminum foil blank; Step S4: heat treating the porous aluminum foil blank; Step S5: coating a thin film solution on the surface of the porous aluminum foil blank after the heat treatment, and performing a drying treatment to form a protective film layer on the surface of the porous aluminum foil blank; Step S6: using a rolling mill to perform a rolling process on the porous aluminum foil blank having the protective film layer in a skew rolling manner to obtain an initial anode foil; Step S7: sintering the initial anode foil to remove the protective film layer to form a sintered foil.
2. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The rolling mill is one of a two-roll rolling mill, a three-roll rolling mill or a four-roll rolling mill, the rolling mill has a rolling roll pressure of 5 μm to 15 μm, and a rolling roll diameter of 65 mm to 600 mm. In step S6, the porous aluminum foil blank having the protective film layer is rolled by the rolling mill in a skew rolling manner to obtain an initial anode foil. The method includes: The porous aluminum foil blank having the protective film layer is subjected to a first rolling treatment, wherein the first rolling treatment is to repeatedly roll the porous aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 20° to 70° with the length direction of the porous aluminum foil blank; The porous aluminum foil blank with the protective film layer is then subjected to a second rolling treatment, wherein the second rolling treatment is to repeatedly roll the porous aluminum foil blank 2 to 20 times when the axial direction of the rolling roller is 110° to 160° with the length direction of the porous aluminum foil blank.
3. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The film solution is an aqueous solution prepared by one or more of hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, polyethylene glycol, polyvinyl alcohol, and polyvinyl pyrrolidone; In step S5, a thin film solution is coated on the surface of the thermally treated porous aluminum foil blank, and the method comprises: The porous aluminum foil blank is coated with the thin film solution on both sides by using a doctor blade coating or screen printing; The thickness of the protective film layer on each side of the porous aluminum foil blank is the same, and the thickness of the protective film layer on each side of the porous aluminum foil blank is 5 μm to 30 μm.
4. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The mass fraction of the water-soluble pore-forming agent to the solid aluminum-containing powder is 0.5% to 4%; the mass ratio of the mixed solution to the solid aluminum-containing powder is 100:(80 to 250); The water-soluble pore-forming agent is one or more of a water-soluble neutral salt, a water-soluble starch, and a water-soluble resin; The water-soluble neutral salt is one or more of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate; The water-soluble starch is one or more of modified corn starch, modified potato starch, modified sweet potato starch, modified cassava starch, modified wheat starch, and modified mung bean starch; The water-soluble resin is one or more of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxyethyl cellulose, hydroxyethyl methyl cellulose and hydroxypropyl methyl cellulose.
5. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: In step S3, the dried aluminum foil blank is washed with water and dried to obtain a porous aluminum foil blank, comprising: The aluminum foil blank is cleaned with deionized water at 10° C. to 80° C. by immersion or ultrasonic cleaning. The cleaned aluminum foil blank is dried at a drying temperature of 40° C. to 120° C.
6. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: In step S4, the porous aluminum foil blank is subjected to heat treatment, including: In an air atmosphere, heating the porous aluminum foil blank from room temperature to 300° C. to 500° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 1 h to 8 h; In a nitrogen, argon or vacuum atmosphere, the porous aluminum foil blank is continuously heated to 570° C. to 600° C. at a heating rate of 0.1° C. / min to 20° C. / min, and kept at this temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
7. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The mass ratio of the solvent, the binder and the additive in the mixed solution is 100:(3-10):(0.5-10); The solvent is a mixture of a first solvent and a second solvent, the first solvent is one or both of terpineol and diethylene glycol butyl ether acetate, and the second solvent is one or more of ethylene glycol, propylene glycol, and glycerol; The binder is one or two of ethyl cellulose and polyvinyl butyral; The additives include one or more of a defoamer, a leveling agent, a dispersant, and a coupling agent. The defoamer is a silicone defoamer or a polyether defoamer, the leveling agent is an acrylic leveling agent, the dispersant is triethanolamine, and the coupling agent is a silane coupling agent.
8. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the aluminum foil substrate is 20 μm to 60 μm, and the aluminum foil substrate has an upper surface and a lower surface that are arranged opposite to each other. In step S2, the aluminum foil blank is formed. The method includes: The aluminum foil substrate is double-sided coated with the aluminum paste to form aluminum paste film layers with the same thickness on the upper surface and the lower surface of the aluminum foil substrate; Under the condition of a drying temperature of 90° C. to 200° C., the aluminum foil substrate having the aluminum paste film layer is dried, and the thickness of the aluminum paste film layer after drying is 50 μm to 60 μm.
9. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: In step S7, the sintering process includes: In a nitrogen, argon or vacuum atmosphere, heating the initial anode foil from room temperature to 610° C. to 650° C. at a heating rate of 0.1° C. / min to 20° C. / min, and keeping the temperature for 4 h to 12 h; After the insulation is completed, cool down with the furnace.
10. The method for preparing an anode foil for an aluminum electrolytic capacitor according to claim 1, characterized in that: After step S7, the method further comprises: The sintered foil is subjected to a water boiling treatment to form an intermediate anode foil, wherein the water boiling treatment comprises boiling the sintered foil in deionized water at 100° C. for 5 to 15 minutes; Performing a chemical formation treatment on the intermediate anode foil to form an oxide layer on the intermediate anode foil to obtain a target anode foil, wherein the chemical formation treatment has a chemical formation voltage of 200V to 700V; The target anode foil is cleaned and dried.
Citation Information
Patent Citations
Aluminum foil for aluminum electrolytic capacitor electrode and method for manufacturing the same
CN102122576A
Preparation method of sintered aluminum foil with high specific volume
CN110814348A
Method for preparing anode foil of aluminum electrolytic capacitor by means of cold rolling machine
CN113458143A
Preparation method of capacitor electrode material
CN117524735A
Method for manufacturing electrode for fuel cell
US5935643A
Cited By
A method for manufacturing an aluminum electrolytic capacitor anode foil and an aluminum electrolytic capacitor
CN122511752A
A method for manufacturing an aluminum electrolytic capacitor anode foil and an aluminum electrolytic capacitor
CN122511752B